Enhancing learning through teachers' pedagogical skills: Self-efficacy, self-regulation, and school climate - R. Anggi Apriyani Usman; Endang Supardi; K. Kusnendi (Inovasi Kurikulum, 2025)
This research is motivated by the student's learning outcomes in the economics of SMA Negeri in Jakarta Timur, which did not reach the Minimum Completeness Criteria (KKM). This research aims to analyze the role of school climate in influencing teachers' pedagogical competence on learning outcomes through students' self-efficacy and self-regulation. The method used is a correlational study with a sample of 138 grade IX social science students selected randomly. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that teachers' pedagogical competence, students' self-efficacy, self-regulation, and school climate are high, while students' economics learning outcomes are moderate. Self-efficacy mediates the effect of teachers' pedagogical competence on learning outcomes. Self-regulation does not mediate this effect. School climate does not moderate the indirect effect of teachers' pedagogical competence through self-efficacy on learning outcomes. School climate also does not moderate the indirect effect of teachers' pedagogical competence through self-regulation on learning outcomes. AbstrakPenelitian ini dilatarbelakangi oleh hasil belajar ekonomi peserta didik SMA Negeri di Jakarta Timur yang tidak memenuhi Kriteria Ketuntasan Minimum (KKM). Tujuan penelitian ini untuk mengkaji peran iklim sekolah dalam mempengaruhi kompetensi pedagogik guru terhadap hasil belajar melalui efikasi diri dan regulasi diri peserta didik. Metode yang digunakan adalah studi korelasional dengan sampel 138 peserta didik kelas IX IPS yang dipilih secara acak. Data dikumpulkan melalui angket dan dianalisis menggunakan structural equation modeling (SEM). Hasilnya menunjukkan kompetensi pedagogik guru, efikasi diri, regulasi diri peserta didik, dan iklim sekolah berada pada tingkat tinggi, tetapi hasil belajar ekonomi peserta didik berada pada tingkat moderat. Efikasi diri memediasi pengaruh kompetensi pedagogik guru terhadap hasil belajar. Regulasi diri tidak memediasi pengaruh tersebut. Iklim sekolah tidak memoderasi pengaruh tidak langsung kompetensi pedagogik guru melalui efikasi diri terhadap hasil belajar. Iklim sekolah juga tidak memoderasi pengaruh tidak langsung kompetensi pedagogik guru melalui regulasi diri terhadap hasil belajar.Kata Kunci: efikasi diri; hasil belajar; iklim sekolah; kompetensi pedagogik guru; regulasi diri